DAKWAH TAREKAT DAN TATANAN MASYARAKAT MADANI DI ACEH - Iskandar Ibrahim (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2020)
Da'wah is the only movement on Earth that returns human belief to the guidance of revelation, but it does not get the support of the wider community in Aceh. Studies on dakwah so far have not captured the role of the tarekat in supporting the order of civil society. Therefore, murshids are present to strengthen the social order there by cultivating religious-emotions through tarekat media. This study aims to describe the relevance of the da'wah of the tarekat and all its accessories with the efforts to build a civil society structure in Aceh today. This qualitative study focuses on the contribution of the tarekat in strengthening efforts to build a civil society structure in Aceh with a unit of analysis of doctrine, role of figures, contribution of scholarship, social participation and civil society in the Aceh context. The exploration of the tarekat's response to the social-community system arrangement in Aceh was traced through the combining of literature data and the experiences of the author and 3 tarekat leaders. This study produced 3 main findings. First, empowering tarekat da'wah for strengthening the social-community system. Second, developing the potential of the tarekat through intensive practice of Islamic law. Third, the spread of Islamic solutions through local culture. Apart from the pros and cons of the tarekat's contribution, it needs to be considered to encourage the development of a social-community system towards a civil society structure in Aceh.Keywords: da'wah, tarekat, civil society.